(untitled) (Journal of Academic Finance, 2021)
Objective: This paper analyses the relationship between financial system development and economic growth using data from 40 Sub-Saharan African countries over 2004-2015. Methodology: It draws on the Eggoh and Villieu (2013) work to specify a non linear model of growth, which estimated by the Generalized Moment Method system. Results: the relationship between financial development and growth is nonlinear with the bellshape, reflecting the existence of threshold effects in the relationship. Too high level of financial development could harm GDP growth. Financial development thus appears to be a necessary but not sufficient condition for economic growth. Originality: The study takes into account multidimensional character of financial development by constructing a composite indicator that integrates six aspects of financial development by PCA method.